Chemical equilibrium of the magnesium manganese oxide redox system for thermochemical energy storage. (21st September 2022) - Bo, Alessandro; Randhir, Kelvin; Rahmatian, Nima; Klausner, James; Petrasch, Joerg
Highlights: Magnesium manganese oxide is promising for thermochemical energy storage. The equilibrium extent of oxidation is measured via thermogravimetric analysis. Temperature and pressure ranges are 1000–1500 °C and 0.01–0.9 atm respectively. Two Gibbs free energy models show excellent agreement with the experimental data. Reaction enthalpies are −335.3 ± 31.2 kJ/molO2 and −340.8 ± 18.0 kJ/molO2 . Abstract: The magnesium manganese oxide redox system shows great promise for use in grid-scale, long duration thermochemical storage. We measured the equilibrium extent of oxidation, y = y eq, of the MgMnO 2 + y system, in a series of thermogravimetric relaxation experiments. Temperatures and oxygen partial pressure ranges are 1000–1500 °C and 0.01–0.9 atm respectively. The equilibrium oxygen stoichiometry ranges from MgMnO 2.109 at 1500 °C and p O 2 = 0.01 atm to MgMnO 2.672 at 1000 °C and p O 2 = 0.9 atm. The equilibrium extent of oxidation, as a function of temperature and oxygen partial pressure, was matched with two semi-heuristic Gibbs-free energy based models that combine theoretical considerations with experimental observations to extract a functional relation between the chemical potential of oxygen and y eq . We obtained enthalpies of reaction of - 335.3 ± 31.2 kJ / mol O 2 and - 340.8 ± 18.0 kJ / mol O 2 respectively. The entropy of reaction is - 184.8 ± 20.3 J / mol O 2 /K.